Factors associated with antihypertensive medication use and blood pressure control in a rural area in Bangladesh: baseline data from a cluster randomised control trial - Fakir M. Amirul Islam; Elisabeth A. Lambert; Sheikh Mohammed Shariful Islam; M. Ariful Islam; Ralph Maddison; Bruce Thompson; Gavin W. Lambert (BMC, 2021)
Abstract Background The use of antihypertensive medications is critical for controlling high blood pressure. We aimed to investigate associations between socio-demographic factors and antihypertensive medications use, and antihypertensive medications use with different types of drugs use with levels of systolic blood pressure (SBP) and diastolic blood pressure (DBP). Methods For the present report we derived data from the baseline measurements of a cluster randomised control trial on 307 participants with previously diagnosed hypertension from the rural district of Narial in Bangladesh. We measured the participant's current blood pressure levels and recorded antihypertensive medications uses. Associated factors included socio-economic status, diabetes, antihypertensive medications use, and types of drugs and doses used for controlling blood pressure. We applied analysis of variance and logistic regression techniques to identify factors associated with blood pressure. Results Of the total participants, 144 (46.9%) were on antihypertensive medications. After multivariate adjustment, binary logistic regression revealed that employees (odds ratio, (95% confidence interval (CI)) (OR 3.58, 95%CI 1.38-9.28) compared to farmers, and people with diabetes (OR 2.43, 95%CI 1.13-5.26) compared to people without diabetes were associated with a higher proportion of antihypertensive medications use. Of 144 participants on antihypertensive medications, 7 (5%) had taken two doses, 114 (79%) had taken one dose per day and the rest were irregular in medication use. The mean (standard deviation) [min, max] SBP and DBP were 149 (19) mmHg [114, 217] and 90 (10) mmHg [75, 126], respectively. Overall, there was no significant difference in SBP (p = 0.10) or DBP (p = 0.67) between participants with or without antihypertensive medications or using any type of medications (p = 0.54 for SBP and 0.76 for DBP). There was no significant association between antihypertensive medications use and elevated BP levels SBP/DBP≥140/90 mmHg (p = 0.42) Conclusion Less than half of the people with hypertension were on medication. Irrespective of the antihypertensive medications use, most of the participant's blood pressure was high. Further study is needed with a large sample to understand the factors and aetiology of unmanaged hypertension in rural areas of Bangladesh where the prevalence of hypertension is very high.